Hospital-Acquired Pneumonia/Ventilator-Associated Pneumonia and Ventilator-Associated Tracheobronchitis in COVID-19 - Rouzé, Anahita; Nseir, Saad (Seminars in Respiratory and Critical Care Medicine, 2022)
Although few studies evaluated the incidence of hospital-acquired pneumonia (HAP) or ventilator-associated tracheobronchitis in COVID-19 patients, several studies evaluated the incidence of ventilator-associated pneumonia (VAP) in these patients. Based on the results of a large multicenter European study, VAP incidence is higher in patients with SARS-CoV-2 pneumonia (36.1%), as compared with those with influenza pneumonia (22.2%), or no viral infection at intensive care unit (ICU) admission (16.5%). Potential explanation for the high incidence of VAP in COVID-19 patients includes long duration of invasive mechanical ventilation, high incidence of acute respiratory distress syndrome, and immune-suppressive treatment. Specific risk factors for VAP, including SARS-CoV-2-related pulmonary lesions, and bacteria–virus interaction in lung microbiota might also play a role in VAP pathogenesis. VAP is associated with increased mortality, duration of mechanical ventilation, and ICU length of stay in COVID-19 patients. Further studies should focus on the incidence of HAP especially in ICU non-ventilated patients, better determine the pathophysiology of these infections, and evaluate the accuracy of currently available treatment guidelines in COVID-19 patients.
Keywords: ventilator-associated pneumonia; ventilator-associated tracheobronchitis; hospital-acquired pneumonia; COVID-19; SARS-CoV-2; mechanical ventilation